A computational docking analysis of chalcone synthase receptor and substrates in Boesenbergia rotunda / Ragaventhan Sanmugavelan - Ragaventhan , Sanmugavelan (2019)
Boesenbergia rotunda is locally known as Chinese ginger. Its rhizomes resemble fingers, making it known as fingerroot. Previous studies show that its rhizome extracts exhibited anticancer, antiviral, antibacterial and antioxidant properties. Numerous secondary metabolites can be found in the extract which are derived from the flavonoid biosynthetic pathway that involves a number of enzymes. Chalcone synthase (CHS) of B. rotunda (BrCHS) belongs to the type III polyketide synthase. It is a key enzyme involves in the initial stage of the flavonoid biosynthetic pathway. It has broad substrate specificity for diverse starter molecules and generating corresponding products. In this study, computational methods were employed to investigate the enzymatic activity of five BrCHS receptor variants with cinnamoyl-CoA and p-coumaroyl-CoA along with malonyl-CoA, feruloyl-CoA and caffeoyl-CoA as the ligand substrates. Homology models of the five variants of BrCHS receptor were built using YASARA software. ProtParam and SOPMA tools in Expasy webserver were used to predict molecular mass and analyse the secondary structures of BrCHS receptor variants, respectively. HADDOCK 2.2 web server was used for molecular docking the BrCHS receptor variants with the ligand and docked energies were used for the docked conformation analysis. Then, 10 ns molecular dynamics simulations were performed using GROMACS 5.1.4 to verify the docking results based on the root-mean-square deviation (RMSD), root-mean-square fluctuation (RMSF), the radius of gyration and binding free energies. The predicted molecular masses of the five BrCHS receptor variants are in the range of 42 – 44 kDa and secondary structure analysis revealed that the variants mainly comprise of α- helices and random coils. The docking results showed that cinnamoyl-CoA has a higher binding affinity towards BrCHS receptor variants 1, 2 and 3 than p-coumaroyl-CoA. On the other hand, p-coumaroyl-CoA has a higher binding affinity towards BrCHS variants 4 and 5. Trajectory analysis based on RMSD, RMSF and radius of gyration revealed that the protein-ligand complexes were stable throughout the 10 ns simulations. In addition, binding free energy profiles showed a good agreement with the docking results and some experimental data. This study further enhances understandings on the substrate specificity and catalytic activity of the BrCHS in chalcone production.